Bem-estar social e gênero : o Estado entre a família e o trabalho no Brasil - Almeida, Mariana Eugenio (2013)
In this dissertation, we take as reference the feminist critiques to the main theories about the emergence and the development of welfare States, in order to understand to what extent family, work and State are related, under a gender perspective. In a context of changes both in families and in the labor market, we note one of the great tensions of nowadays, that affects women predominantly: the conciliation between paid work and family responsibilities. Accordingly, new challenges are imposed not only to the new families, that have now two providers, but also to the welfare States, whose bases began to be questioned. Thus, in this dissertation we intend to investigate how family characteristics and the scope of public welfare provision can be related to female participation in the labor force. Enlightened by the literature studied and the international data analyzed, we turn our looks to Brazil, highlighting the development of family policies in the country and the changes that took place in the families and in the labor market. The empirical analysis was made using data from the Demographic Census 2010, which was conducted by the Brazilian Institute of Geography and Statistics. We attempted, through a descriptive analysis of the data, to show the changes that have occurred in both families and labor market in Brazil and in Minas Gerais state, in order to understand the impact that those changes may have on the public institutions of welfare. In a second moment, econometric models were estimated, aiming at an exploratory analysis of the effect of certain variables related to the family and the State, on female participation on the labor market. The results suggest that female paid work is sensible to the type of family she belongs to and, moreover, that childcare has a positive effect on female participation in labor market. In this sense, it is evident the importance of family policies that contribute to the conciliation between paid work and family responsibilities in Brazil. The absence of such policies tends to reinforce inequalities between men and women in Brazil, once it hinders female participation on labor market, especially for poor families.